Impact of Intellectual Capital on Financial Performance of Listed Oil and Gas Firms in Nigeria - AbdulRahman, Sani Bala; Abubakar, Aminu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This paper examines the impact of intellectual capital on financial performance of listed firms in Nigeria. To achieve this objective; quantitative research design was employed. Data were generated from the annual reports and accounts of the sampled listed oil and gas companies from 2016-2020. The period is chosen and believes to be adequate in providing insight on the inflationary trends which the industry experienced. Similarly, the period of five years selected is in line with the studies of Muhammad and Rashid, 2015 as well as Iyande, 2018. Intellectual Capital as independent variable was measured by its components (HCE, SCE and CEE) while financial performance being the dependent variable was measured by NPM and ROE. Regression technique was used as tools of data analysis and the findings establish that the independent variables (HCE, SCE and CEE) have significant positive impact on the oil and gas companies’ Financial Performance proxies by NPM and ROE. The regression results show R-square of 86.1% and 59.4% for NPM and ROE models respectively. This implies that the model is fit and the explanatory variables are properly selected and account for the substantial value of the corporate profitability. Hence, the paper recommends that listed oil and gas companies in Nigeria should improve their efforts to boost the value of their intellectual capital for its crucial impact on NPM and ROE. This can be achieved through maximization of market value created, intellectual capital return and more investment in intellectual capital components, particularly human, structural and relational/customer capital.